Comparison of the efficacy and safety of laparoendoscopic single-site surgery with conventional laparoscopic surgery for upper ureter or renal pelvis stones in a single institution: a randomized controlled study - Juhyun, Park; Seung, Bae Lee; Sung, Yong Cho; Chang, Wook Jeong; Hwancheol, Son; Yong, Hyun Park; Hyeon, Hoe Kim; Ab Rashid, Islah Munjih; Hyeon, Jeong (UROL & NEPHROL RES CTR-UNRC, 2016)
Purpose: To evaluate the utility and safety of laparoendoscopic single-site surgery (LESS) in comparison with conventional laparoscopic (CL) surgery for the treatment of upper urinary tract stones. Material and Methods: Between June 2011 and May 2012, 20 patients with upper urinary tract stones were included in this prospective randomized study. The patients were assigned into the LESS group or CL group in a one-on-one manner using a random table. The clinical parameters were evaluated in the immediate postoperative period, and the stone clearance rate was evaluated via non-contrast computer tomography at one month postoper- atively. Results: There were no significant differences in patient demographics or preoperative stone sizes between the two groups. The perioperative parameters, including operative time, estimated blood loss, postoperative pain scores, length of hospital stay, and changes in renal function, were comparable. No transfusions or open conversions were required in either group. The incidence of residual stones was lower in the LESS group (1 case) than in the CL group (2 cases). However, this difference was not statistically significant. Conclusions: For large and impacted upper ureteral stones, the effectiveness and safety of LESS were equivalent to those of CL. Further randomized control trials with larger sample sizes are needed to strengthen the conclusions of this study.